Inkjet printing processing conditions for bulk-heterojunction solar cells using two high-performing conjugated polymer donors - Hermerschmidt, Felix; Papagiorgis, Paris; Savva, Achilleas; Christodoulou, Constantinos; Itskos, Grigorios; Choulis, Stelios A. (My University, 2014)
We report the processing conditions for inkjet-printed active layers of organic photovoltaic (OPV) devices comprising bulk-heterojunction blends of the low bandgap conjugated polymer poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b: 2′,3′-d]silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1, 3-benzothiadiazole)-5,5′-diyl] (Si-PCPDTBT) as well as poly[N-9′-hepta-decanyl-2,7-carbazole-alt-5,5-(4′, 7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT) used as electron donors with [6,6]-phenyl-C71-butyric acid methyl ester (PC 70BM) as electron acceptor. By controlling the inkjet printing processing conditions, we gain a significant improvement in device power conversion efficiency (PCE) to previously reported work using these materials. We obtain Si-PCPDTBT:fullerene and PCDTBT:fullerene-based inkjet-printed OPVs with power conversion efficiency of ~3% and ~4%, respectively.
Keywords: Conjugated polymers; Inkjet printing and processing; Morphology; Organic photovoltaics; Printed electronics